Selectively Fluorinated Furan‐Phenylene Co‐Oligomers Pave the Way to Bright Ambipolar Light‐Emitting Electronic Devices. (27th August 2021) - Koskin, Igor P.; Becker, Christina S.; Sonina, Alina A.; Trukhanov, Vasiliy A.; Shumilov, Nikita A.; Kuimov, Anatoly D.; Zhuravleva, Yuliya S.; Kiseleva, Yuliya O.; Shundrina, Inna K.; Sherin, Peter S.; Paraschuk, Dmitry Yu.; Kazantsev, Maxim S.
Abstract: Linearly conjugated oligomers attract ever‐growing attention as promising systems for organic optoelectronics because of their inherent lucky combination of high charge mobility and bright luminescence. Among them, furan‐phenylene co‐oligomers (FPCOs) are distinguished by outstanding solubility, very bright luminescence, and good hole‐transport properties; however, furan‐containing organic semiconductors generally lack electron transport, which makes it impossible to utilize them in efficient light‐emitting electronic devices, specifically, ambipolar light‐emitting transistors. In this work, 1, 4‐bis(5‐phenylfuran‐2‐yl)benzene (FP5) derivatives are synthesized with the fully/partially fluorinated central and edge phenyl rings. It is shown that the selective fluorination of FPCOs lowers the energies of frontier molecular orbitals, maintaining the bandgap, solubility, and bright luminescence, dramatically improves the photostability, tunes the π‐π stacked packing, and allows the first realization of electron transport in FPCOs. It is found that selectively fluorinated 2, 2′‐(2, 3, 5, 6‐tetrafluoro‐1, 4‐phenylene)bis[5‐(3, 5‐difluorophenyl)furan] demonstrates well‐balanced ambipolar charge transport and efficient electroluminescence in an organic light‐emitting transistor (OLET) with external quantum and luminous efficiencies as high as 0.63% and 5 cdA −1, respectively, which are among the best reported for OLETs. The findings show that "smart" fluorination is a powerful tool to fine‐tune the stability and performance of linearly conjugated small molecules for organic optoelectronics. Abstract : Furan‐phenylene co‐oligomers commonly show inherent bright luminescence, enhanced molecular rigidity, but only p‐type charge transport. Their selective fluorination improves the crystal packing, dramatically enhances the photostability, and provides well‐balanced ambipolar charge transport. As a result, the optimally fluorinated oligomer demonstrates efficient electroluminescence in ambipolar single‐layer organic light‐emitting transistors.